DAMPAK MEDIA SOSIAL TERHADAP PERILAKU SOSIAL REMAJA SMAN 21 MEDAN - Permata Amalia Mursyid; Putra Apriadi Siregar (CV. Adiba Aisha Amira, 2023)
In recent decades we often hear the word social media or social media or social networks. The arrival and development that is increasingly rapid by relying on technology has become a guideline for developing individuals. Adolescents who are the future of the nation with the development of digitalization of the environment cause adolescents to have the potential to have a positive or negative impact. This study uses a quantitative descriptive method. The purpose of this study was to determine the impact of social media on the social behavior of adolescents at SMAN 21. The results of this study were 90.9% of SMAN 21 students had a negative impact on social media because lying down too often or playing cellphones while lying down can cause muscles to become weak and 96.93% feel bored using social media. The conclusion that researchers can draw in this study is the impact of social media on the social behavior of adolescents at SMAN 21 MEDAN which has both good and bad effects, where from the positive side, teenagers open social media while learning to get new things on social media and make lots of friends from using the media. social media that can strengthen relationships with each other anywhere and anytime.